Strategi Dan Skala Kesantunan Tindak Direktif Mahasiswa Riau Di Lingkungan Masyarakat Berlatar Belakang Budaya Jawa - Lestari, Puji; , Prof. Dr. Harun Joko Prayitno.,M.Hum (2016)
This research has three purpose. 1. Describe the use of Riau students follow up strategy directive in the environmental community behind Java culture. 2. Expose the level of politeness of Riau students follow the directive in the community environment set in Javanese culture based on the scale of politeness. 3. Describe the implications of research combining characters in college. This type of research including qualitative descriptive. Research data in the form of lingual units follow said the directive either in formal or informal atmosphere around the region of Surakarta. As for the data source includes student activities of Riau from UMS, UNS, and IAIN as many as 15 people. Using the technique of gathering techniques refer, record, and note. Data analysis methods in accordance with the pragmatic good intralingual and ekstralingual. Interpretation of the embodiment of the strategy follow the directive is done with reference to the analysis of the workings of Prayitno and politeness scale analysis based on the model of post-translational modification technique achieved by Lakoff and read engineering landmark. The results of the research there are three things. 1) Riau Students when masyarakar set to speak Javanese culture more use of indirect strategy than direct comparison (66,7% 33.3%): 2) analysis of politeness scale refers to the results of the politeness strategy category in terms of politeness levels low, medium, and fine. The combination of politeness strategy with student Riau politeness scale has a low level of politeness by comparison (47%: 23%: 30%). Total data on the scale of politeness directive based on the strategy of direct and indirect politeness levels low for as many as 14 data, the level of politeness are as many as 7 data, and the level of politeness is good as much as 9 data. 3) Implications of the research can be used as teaching material composing characters in college courses, in Indonesian Language speaking skills and listening material. Listening and speaking skills competency demands students to communicate in manners. Learning to be enjoyable when using polite language. Keywords: implications, the scale, and politeness strategy for the directive.